Facial Moulage Fabrication Using a Two-Stage Poly(vinyl siloxane) Impression - Abdullah S. Alsiyabi, BDS, MS;1 and Glenn E. Minsley, DMD2 (Journal of Prosthodontics, 2006)
Traditional techniques for the fabrication of a facial moulage have relied on materials with various shortcomings.